From Organizational Culture to Psychological Flourishing: The Mediating Role of Employee Well-being in Higher Education - Sunarsih Sunarsih; Lailatul Izzah; Raspan Hamdi; Arifin Arifin (Journal of Educational Studies, 2026)
This study examines the structural relationships among organizational culture, employee well-being, and psychological flourishing in higher education. Grounded in Denison’s cultural framework and the PERMA model of well-being, the research proposes that employee well-being mediates the relationship between organizational culture and flourishing. A quantitative explanatory design was employed involving 210 lecturers from private universities in Pekanbaru, Indonesia. Data were analysed using Partial Least Squares Structural Equation Modelling (PLS-SEM). The findings indicate that organizational culture has a strong and significant positive effect on employee well-being (? = 0.733, p < 0.001). Employee well-being significantly predicts psychological flourishing (? = 0.276, p < 0.01). However, organizational culture does not have a significant direct effect on flourishing. Mediation analysis reveals that employee well-being fully mediates the relationship between organizational culture and psychological flourishing. The model explains 53.7% of the variance in employee well-being and 7.4% of the variance in flourishing. These results suggest that institutional culture enhances flourishing primarily through strengthening lecturers’ multidimensional well-being. This limitation should be more explicitly acknowledged to avoid overstating the model’s explanatory power. The study contributes to positive organizational scholarship by integrating cultural theory, PERMA-based well-being, and flourishing into a unified framework within the higher education context